2008
DOI: 10.1128/iai.00410-08
|View full text |Cite
|
Sign up to set email alerts
|

Outer Surface Protein A Protects Lyme Disease Spirochetes from Acquired Host Immunity in the Tick Vector

Abstract: The Lyme disease spirochete Borrelia burgdorferi alters the expression of outer surface protein (osp) genes as the bacterium cycles between ticks and mammals. OspA is produced as borreliae enter the tick vector and remains a major surface antigen during midgut colonization. To elucidate the role of OspA in the vector, we created an insertional deletion of ospA in strain B31-A3. The ospA mutant infects mice when it is injected intradermally and is acquired by larval ticks fed on these mice, where it persists th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
82
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 69 publications
6
82
0
Order By: Relevance
“…In contrast, OspB could substitute for OspA during tick colonization. Our data provide further evidence supporting the conclusion of Battisti et al (18) that a significant role of OspA is to protect spirochetes in the tick midgut from ingested mammalian antibodies, while we also demonstrate that OspA plays a significant role in tick colonization in the absence of specific antibody.…”
supporting
confidence: 79%
See 3 more Smart Citations
“…In contrast, OspB could substitute for OspA during tick colonization. Our data provide further evidence supporting the conclusion of Battisti et al (18) that a significant role of OspA is to protect spirochetes in the tick midgut from ingested mammalian antibodies, while we also demonstrate that OspA plays a significant role in tick colonization in the absence of specific antibody.…”
supporting
confidence: 79%
“…OspA is required for normal tick colonization (18)(19)(20). Previous studies have demonstrated that OspA binds to a tick midgut receptor (TROSPA) (21) and protects spirochetes from the tick midgut environment, including antibodies against invariant B. burgdorferi surface components entering with a blood meal from an infected animal (18).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Notable shifts include the down-regulation of surface protein ospA and the up-regulation of ospC (Marconi et al, 1993;Ohnishi et al, 2001;Schwan et al, 1995;Schwan and Piesman, 2000). OspA interacts with a protein in the tick gut to facilitate spirochete colonization in tick gut epithelium (Pal et al, 2004) and protects the spirochetes from host-derived bacteriacidal antibodies (Battisti et al, 2008). The upregulation of ospC reduces the effect of the host adaptive immune response to kill the spirochetes in the tick's midgut while feeding, effectively evading the host's immune system and aiding in dissemination; however, the precise mechanism is still unknown (Randolf and Caimano, 2008).…”
Section: Borrelia Infection In the Vertebrate Hostmentioning
confidence: 99%